Memantine: New prospective in bipolar disorder treatment - Serra, Giulia (World J Psychiatry, 2014)
We review preclinical and clinical evidences strongly suggesting that memantine, an old drug currently approved for Alzheimer’s dementia, is an effective treatment for acute mania and for the prevention of manic/hypomanic and depressive recurrences of manic-depressive illness. Lithium remains the first line for the treatment and prophylaxis of bipolar disorders, but currently available treatment alternatives for lithium resistant patients are of limited and/or questionable efficacy. Thus, research and development of more effective mood stabilizer drugs is a leading challenge for modern psychopharmacology. We have demonstrated that 21 d administration of imipramine causes a behavioural syndrome similar to a cycle of bipolar disorder, i.e., a mania followed by a depression, in rats. Indeed, such treatment causes a behavioural supersensitivity to dopamine D2 receptor agonists associated with an increase sexual activity and aggressivity (mania). The dopamine receptor sensitization is followed, after imipramine discontinuation, by an opposite phenomenon (dopamine receptor desensitization) and an increased immobility time (depression) in the forced swimming test of depression. Memantine blocks the development of the supersensitivity and the ensuing desensitization associated with the depressive like behavior. On the basis of these observations we have suggested the use of memantine in the treatment of mania and in the prophylaxis of bipolar disorders. To test this hypothesis we performed several naturalistic studies that showed an acute antimanic effect and a long-lasting and progressive mood-stabilizing action (at least 3 years), without clinically relevant side effects. To confirm the observations of our naturalistic trials we are now performing a randomized controlled clinical trial. Finally we described the studies reporting the efficacy of memantine in manic-like symptoms occurring in psychiatric disorders other than bipolar. Limitations: A randomized controlled clinical trial is needed to confirm our naturalistic observations. Conclusion: We believe that this review presents enough pharmacological and clinical information to consider the administration of memantine in the treatment of bipolar disorders that no respond to standard mood stabilizers.